Tech-Enhanced Language Learning: Bridging Linguistics and Education - Kadek Adyatna Wedananta; I Gusti Ayu Indah Triana Juliari; Anak Agung Adi Wiryya Putra (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2025)
The research titled Tech-Enhanced Language Learning: Bridging Linguistics and Education explores the transformative role of technology in language education, emphasizing its intersection with linguistic theories and pedagogical practices. This study investigates how digital tools and resources can enhance language acquisition, improve learner engagement, and foster effective teaching methodologies. Through qualitative data collected from educators and learners, the research identifies key benefits of technology integration, including increased motivation, personalized learning experiences, and the facilitation of collaborative learning environments. Additionally, the study addresses challenges such as unequal access to technology and the need for teacher training. The findings underscore the importance of a balanced approach that combines traditional teaching methods with innovative technological solutions. Ultimately, this research contributes to the ongoing discourse on the future of language education, advocating for the strategic implementation of technology to enrich linguistic learning experiences and outcomes.